INFLUENCE OF CULTURE IN STUDENT CAREER PLANNING - Ifrah Hifsy; Daharnis; Mega Iswari (Literasi Nusantara, 2022)
Culture is a mindset that is embedded in individuals through their habits that are obtained from the environment. While career planning is a process of selecting career goals, taking into account the opportunities, opportunities, constraints and career choices to achieve the desired career goals in accordance with the talents, interests and potential of students. So, the culture that is used or the individual will affect the career planning of an individual or student. This study aims to determine whether there is a cultural influence in career planning. And in this study, culture is quite influential in individual or student career planning.